Synoviocyte cultures from synovial fluid - L. Punzi; A. Pozzuoli; F. Calabrese; R. Luisetto; R. Ramonda; L. Braghetto; F. Oliviero; A. Scanu (PAGEPress Publications, 2011)
The study of the pathogenetic mechanisms of rheumatic diseases is in general carried out through "in vitro" systems based on cellular cultures models. The difficulties to achieve fresh human tissue prompted us to develop a simpler method to obtain fibroblast-like synovial cells from synovial fluid (SF). Methods: SF was collected from the knees of 5 patients with rheumatoid arthritis (RA), 4 with osteoarthritis (OA) and 5 with psoriatic arthritis (PsA). The pellet obtained after centrifugation was resuspended in DMEM/HamF12 containing 10% fetal calf serum, 1% peni-streptomicin, 4ng/ml of fibroblast grow factor and incubated at 37°C in T25 culture flasks. Synoviocytes were also obtained from fresh synovial membranes (SM) by explants technique. Both types of cells were characterized by immunocytochemistry and their inflammatory response to synthetic monosodium urate crystals was studied through the measurement of nitric oxide (NO). Results: Adherent synoviocytes were obtained from the culture of 2/5 SF from RA, 4/4 SF from OA and 5/5 SF from PsA. Synoviocytes isolated from both SF and SM expressed surface antigens CD90, CD55, and the intracellular prolyl- 4-hydroxylase. Morphologically, the cells showed the typical spindle-shape fibroblast-like appearance. NO levels induced by UMS crystals in SF synoviocytes were similar to those obtained in SM synoviocytes. Conclusion: Adherent cells obtained from SF showed the phenotype and the reactivity of tissue synoviocytes. Due to the easy accessibility of SF, this method may represents an useful alternative when synovial tissues is not promptly available.